2014
DOI: 10.1017/s0047279414000634
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets the Top Jobs? The Role of Family Background and Networks in Recent Graduates’ Access to High-status Professions

Abstract: There is currently a debate in policy circles about access to "the upper echelons of power" (Sir John Major, ex Prime Minister, 2013). This research seeks to understand the relationship between family background and early access to top occupations. We find that privately educated graduates are a third more likely to enter into high status occupations than state educated graduates from similarly affluent families and neighbourhoods. A modest part of this difference is driven by educational attainment with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
116
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 50 publications
(60 reference statements)
13
116
0
3
Order By: Relevance
“…If they did have multiple outcomes, or work on a temporary basis this was something that did not tend to last for more than a twelve month period. These findings partially support those from a study by Macmillan, Tyler and Vignoles (2013). They found that socioeconomic status affects the likelihood of a recent graduate accessing a top job e.g.…”
Section: Pre-entry Characteristics Influenced a Graduate Trajectorysupporting
confidence: 89%
“…If they did have multiple outcomes, or work on a temporary basis this was something that did not tend to last for more than a twelve month period. These findings partially support those from a study by Macmillan, Tyler and Vignoles (2013). They found that socioeconomic status affects the likelihood of a recent graduate accessing a top job e.g.…”
Section: Pre-entry Characteristics Influenced a Graduate Trajectorysupporting
confidence: 89%
“…To separate that part which may be related to human capital investment we also compute a dummy for having attended a private school before university. Private schools are expensive and tend to affect labour market outcomes positively, representing an investment on the part of the parents (Macmillan, Tyler, and Vignoles 2015).…”
Section: Parental Backgroundmentioning
confidence: 99%
“…Thus, major groups 1 and 2 (i.e. managers and professionals) are regarded as the "high-status" occupations (Bukodi and Goldthorpe 2011;Macmillan et al 2015). But, given the possibility that many other jobs outside these two groups are now utilising graduates' skills, for a classification of graduate jobs, it is necessary to go beyond the traditional notion of high status.…”
Section: The Concept and Indicators Of A "Graduate Job"mentioning
confidence: 99%